Industry-Science Cooperation in France and in Poland - the Objectives of the Europe 2020 Strategy and their Implementation at the National Level - Czyżewska-Misztal, Dorota (DEMO, 2016)
Industry-science cooperation is considered to be one of the key measures to strengthen innovativeness and competitiveness of national economies. Fostering industryscience linkages seems particularly important from the perspective of the implementation of the Europe 2020 strategy. Th e aim of the paper is to review national reform programmes in Poland and in France (from the period 2011-2015) in terms of objectives and actions in the fi eld of industry-science cooperation. Descriptive analysis and analysis of strategic documents are research methods implemented in the paper. Th e paper shows that the objectives and actions in the fi eld of industry-science cooperation are similar in both countries even if they signifi cantly diff er in terms of innovation performance. Moreover, the similarities are visible especially in the support for competitiveness clusters in France and clusters in Poland.(original abstract)